2016
DOI: 10.1016/j.enbuild.2016.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Eco-costs evaluation for the optimal design of buildings with lower environmental impact

Abstract: At present, most products and processes are optimized according only to their economic performance and disregarding environmental aspects. To promote a more sustainable economy, however, the environmental performance should be accounted for in the analysis. Here we present a methodology based on the use of eco-costs to translate the environmental impact of a building into monetary units that are incorporated explicitly into its economic performance assessment. The capabilities of the methodology presented are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In the literature, the application of life cycle assessment to the OTWRB is becoming more and more popular [16,21,62]. Based on this theory, three indicators in the paper, which are life cycle cost (LCC), life cycle primary energy demand (LPED) and life cycle global warming potential (LGWP), are selected to present the impacts of the ITEWB on these three aspects.…”
Section: Calculation Of Operational Energy Consumption Of the Hypothementioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the application of life cycle assessment to the OTWRB is becoming more and more popular [16,21,62]. Based on this theory, three indicators in the paper, which are life cycle cost (LCC), life cycle primary energy demand (LPED) and life cycle global warming potential (LGWP), are selected to present the impacts of the ITEWB on these three aspects.…”
Section: Calculation Of Operational Energy Consumption Of the Hypothementioning
confidence: 99%
“…Insulation thickness is an important parameter to consider when applying thermal insulation, thus, there is considerable research about the optimal insulation thickness of the external walls for residential buildings (OTWRB) [14][15][16][17][18]. Since the climate is one of the most important factors in determining the OTWRB [19][20][21], it is necessary to cut down the scope of the contest to the HSCW zone of China for the OTWRB recommended in this certain area. However, until recently, a few researchers began to pay attention to the OTWRB in this special part of China.…”
Section: Introductionmentioning
confidence: 99%
“…Also it is noticeable to mention that in many simulation-based studies the parametric analysis is unfairly referred as optimization; however, to the best of authors knowledge, no report was found so far using optimization algorithms to optimize the e.g. PCM melting point temperature, and very few literature is available on the multi-dimensional analysis [74] and until now little importance has been given to single-and multi-objective mathematical optimizations [101] and there few cases of multi-objectives optimization of PCM-enhanced passive buildings, however, recently more attention has been paid to simulation-based optimization of passive PCM buildings to increase the thermal comfort and energy performance of building [106], to optimization the thickness of insulation and PCM layers [121], and to investigate the life cycle and environmental impact of building with PCM [123][124][125]. Parametric analysis may help to find the best solution among the available options but not always the optimum solution and it is time consuming.…”
Section: Technical Barriersmentioning
confidence: 99%
“…The results show that, among all stages, the environmental cost of the material production stage is higher than that of any other stages. A method translating the environmental impact into monetary units was composed by Carreras et al [17]. The approach used eco-cost indicators to quantify the cost to prevent a given amount of environmental burden.…”
Section: Introductionmentioning
confidence: 99%